2024
DOI: 10.1002/adem.202301052
|View full text |Cite
|
Sign up to set email alerts
|

Passivating Polycrystalline Copper with an Ultrathin Samarium Layer

Szymon Abrahamczyk,
Marc Walker,
Yisong Han
et al.

Abstract: We report how a layer of samarium (Sm) with a thickness equivalent to ∼ 2 atoms (0.8 nm) deposited by thermal evaporation is remarkably effective at passivating polycrystalline copper (Cu) towards oxidation in ambient air. To monitor the rate of Cu oxidation in real time, slab‐like Cu films with a thickness of 9 nm were fabricated on glass modified with a layer of 3‐mercaptopropyl silatrane, which immobilises condensing Cu atoms by reaction with the thiol moiety, promoting slab‐like film formation at very low … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 77 publications
0
1
0
Order By: Relevance
“…From the atomic resolution STEM image of Figure d, it is observed that the average thickness of the SMSI overlayer is 1.9 ± 0.2 nm. The amorphous Sm 2 O 3 layer can be associated with the inherent defects such as oxygen deficiency. The higher work function of nickel (5.0–5.3 eV) compared to reducible oxide Sm 2 O 3 (2.7–2.8 eV) facilitates the electron transfer from Sm 2 O 3 to Ni within the Ni/Sm 2 O 3 system. , As proposed by Fu et al, this electron transfer drives the transport and migration of Sm 2 O 3 species over Ni nanoparticles, resulting in the formation of an encapsulating layer . Therefore, with annealing at H 2 /N 2 = 1:4, the surface of Ni nanoparticles would be covered with Sm 2 O 3 through a surface diffusion process.…”
Section: Results and Discussionmentioning
confidence: 98%
“…From the atomic resolution STEM image of Figure d, it is observed that the average thickness of the SMSI overlayer is 1.9 ± 0.2 nm. The amorphous Sm 2 O 3 layer can be associated with the inherent defects such as oxygen deficiency. The higher work function of nickel (5.0–5.3 eV) compared to reducible oxide Sm 2 O 3 (2.7–2.8 eV) facilitates the electron transfer from Sm 2 O 3 to Ni within the Ni/Sm 2 O 3 system. , As proposed by Fu et al, this electron transfer drives the transport and migration of Sm 2 O 3 species over Ni nanoparticles, resulting in the formation of an encapsulating layer . Therefore, with annealing at H 2 /N 2 = 1:4, the surface of Ni nanoparticles would be covered with Sm 2 O 3 through a surface diffusion process.…”
Section: Results and Discussionmentioning
confidence: 98%